2016
DOI: 10.5144/0256-4947.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognosis of stent thrombosis following percutaneous coronary intervention in Middle Eastern patients: The First Jordanian Percutaneous Coronary Intervention Registry (JoPCR1)

Abstract: BACKGROUNDThe incidence, risk factors, and outcome of stent thrombosis (ST) after percutaneous coronary intervention (PCI) in Middle Eastern patients are largely unknown.OBJECTIVETo determine the incidence, risk factors and outcome in our population.DESIGNRetrospective study of a prospective multicenter registry of consecutive patients who underwent PCI between January 2013 and February 2014 (JoPCR1).SETTING12 tertiary care centers in Amman and Irbid, Jordan.PATIENTS AND METHODSWe collected clinical baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Moreover, efforts to prevent or reduce possible complication post‐cardiac intervention and encourage healthy lifestyle choices are not well established in Jordan (Mosleh & Almalik ; Saleh et al. ). Thus, studies like the current one might stimulate clinicians and policy makers to step forward in designing and approving national educational guidelines applicable for patients who undergo PCI and open‐heart surgery.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, efforts to prevent or reduce possible complication post‐cardiac intervention and encourage healthy lifestyle choices are not well established in Jordan (Mosleh & Almalik ; Saleh et al. ). Thus, studies like the current one might stimulate clinicians and policy makers to step forward in designing and approving national educational guidelines applicable for patients who undergo PCI and open‐heart surgery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, efforts to prevent or reduce possible complication post-cardiac intervention and encourage healthy lifestyle choices are not well established in Jordan Saleh et al 2016…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, 30 patients (60%) were diabetics, which is higher than what was reported in other studies. 9 The high prevalence of diabetes in our patients reflects the practice of PCI in our region since most patients prefer to have a PCI even if it is against the recommendations. Additionally, heart surgery centers are not evenly distributed in our country, and many patients are referred to us from remote areas where surgery is not available .…”
Section: Discussionmentioning
confidence: 86%
“…[10][11][12][13] The recently completed first Jordanian PCI Registry (JoPCR1) assessed the in-hospital and one-year outcomes in patients who underwent PCI for ACS and stable coronary disease. [14][15] We used data from this registry to evaluate the incidence, clinical and coronary angiographic features, predictive factors, in-hospital and one-year prognosis in patients who developed HF during the hospital stay compared with those who did not.…”
Section: Introductionmentioning
confidence: 99%